2001
DOI: 10.1002/1097-0142(20010101)91:1<178::aid-cncr23>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in cancer diagnosis and survival

Abstract: BACKGROUND Concern has been raised over the disproportionate cancer mortality among minority and low‐income persons. The current study examined differences in disease stage at the time of diagnosis and subsequent survival for patients who are medically indigent compared with the rest of the population of cancer patients in Michigan. METHODS The authors linked three Michigan statewide data bases: the Cancer Registry, Medicaid enrollment files, and death certificates. The analysis focused on female breast, cervi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
163
3
3

Year Published

2002
2002
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 234 publications
(175 citation statements)
references
References 23 publications
6
163
3
3
Order By: Relevance
“…In striking contrast to studies that demonstrated an association between nonwhite race and inferior cancer care and, ultimately, unfavorable long-term survival, [14][15][16][17][18][19][20][21] we observed that nonwhite race predicted improved surgical care, as defined by adequate lymph node evaluation. Because African Americans and Hispanics tend to be uninsured and of lower socioeconomic status, it is possible that university centers are the likely providers of their surgical care: These findings are contrary to popular opinion.…”
Section: Discussioncontrasting
confidence: 99%
“…In striking contrast to studies that demonstrated an association between nonwhite race and inferior cancer care and, ultimately, unfavorable long-term survival, [14][15][16][17][18][19][20][21] we observed that nonwhite race predicted improved surgical care, as defined by adequate lymph node evaluation. Because African Americans and Hispanics tend to be uninsured and of lower socioeconomic status, it is possible that university centers are the likely providers of their surgical care: These findings are contrary to popular opinion.…”
Section: Discussioncontrasting
confidence: 99%
“…These factors include a low income, Medicaid enrollment, lack of private health insurance, poor transportation, beliefs that women who have breast surgery are no longer attractive to men, beliefs that air causes a cancer to spread, beliefs that chiropractic is effective treatment for breast cancer. 46,47 …”
Section: Socioeconomic Cultural and Behavioral Factorsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Several reasons have been suggested, including socieoeconomic and cultural factors, cancer biology, differential treatment intensity, pharmacogenetics and comorbid conditions. [8][9][10][11][12] Data from hematologic malignancies such as AML also demonstrate poorer survival and worse CR rates in African Americans, specifically men, compared with African American women and whites. 13 A subsequent study did not find any significant differences in the type or intensity of post-remission therapy after AML induction.…”
Section: Introductionmentioning
confidence: 99%